Facilitating innovation: The role of the centre for construction innovation - Abbott, Carl; Allen, Stephen (International Journal of Strategic Property Management, 2010)
This case‐study outlines the activities of the Centre for Construction Innovation highlighting critical success factors associated with collaborative centres and innovation brokers in transferring knowledge between Universities and Industry. The case study also explains the national context in which the centre has developed. The Centre's approach to the provision of knowledge and tools to create an industry environment that fosters innovation is presented and discussed. The Centre brings together industrialists and academics as multi‐disciplinary participants in a range of best practice education and training, seminars, workshops and in‐company events, facilitating change by learning, debate and experience. The Centre recognises the complex relationship that exists between projects, organisations, people and contracts and this in turn determines both what is possible and what is desirable. The collaborative process that seeks to achieve desirable outcomes requires inter‐ and intra‐ organisational cultural assessment and development. Facilitating this is a key role of the Centre.First Published online: 18 Oct 2010